2022
DOI: 10.1029/2021ef002402
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Radiative Forcing, Not Sensitivity, Explain Differences in Summertime Land Temperature Variance Change Between CMIP5 and CMIP6

Abstract: Increased frequency of extreme high temperatures is largely attributable to increases in mean temperature (Huntingford et al., 2013;Rhines & Huybers, 2013). Although significant changes in summertime temperature variance have not been observed in the historic record (McKinnon et al., 2016), climate model simulations generally indicate greater summertime temperature variance in a warming climate (e.g., Duan et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Previous studies have found that there was a warming hiatus from 1998 to 2012, whereas other studies suggest a warming hiatus occurred from 2000 to 2014 (Fyfe et al., 2016; Karl et al., 2015; Knight et al., 2009). Hypothesized reasons for warming‐trend slowdown include changes in radiative forcing processes (Guan et al., 2015), and the models were more sensitive to radiative forcing due to suppressed surface evapotranspiration in CMIP6 models, which could cause the uncertainty of model simulation results of past and future air temperature change (Chan et al., 2022; Fyfe et al., 2021). However, warming trends were significant from 1980 to 2014 with 0.349°C/decade.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that there was a warming hiatus from 1998 to 2012, whereas other studies suggest a warming hiatus occurred from 2000 to 2014 (Fyfe et al., 2016; Karl et al., 2015; Knight et al., 2009). Hypothesized reasons for warming‐trend slowdown include changes in radiative forcing processes (Guan et al., 2015), and the models were more sensitive to radiative forcing due to suppressed surface evapotranspiration in CMIP6 models, which could cause the uncertainty of model simulation results of past and future air temperature change (Chan et al., 2022; Fyfe et al., 2021). However, warming trends were significant from 1980 to 2014 with 0.349°C/decade.…”
Section: Discussionmentioning
confidence: 99%
“…So far, this model is identical to the one presented in [19], but one final alteration is required to (8). Figure 4 shows that when the surface soil is depleted, the latent heat flux does not approach zero.…”
Section: Derivation Of Smacm Model Equationsmentioning
confidence: 99%
“…This owes to the fact that deep, root-level soil moisture is present, and contributes to the latent heat flux. We therefore add an additional soil moisture fraction to (8) to capture this e↵ect, denoted as m 0 , resulting in the final temperature evolution equation,…”
Section: Derivation Of Smacm Model Equationsmentioning
confidence: 99%
See 1 more Smart Citation